A Translation Analysis Of Adjective Phrase In A Textbook Inside The Kingdom By Carmen Bin Ladin And Its Translation Into Kisah Hidupku Di Arab Saudi - Hidayah, Defita Permata Sari (2012)
This research examines a translation analysis of adjective phrase in Inside the Kingdom into Kisah Hidupku di Arab Saudi. It used a descriptive-qualitative, i.e., describing the accuracy (equivalency), readability (clearness), and naturalness (acceptability) of the adjective phrase translation. The data source is a text entitled Inside the Kingdom by Carmen Bin Ladin and Its Translation into Kisah Hidupku di Arab Saudi, Inside the Kingdom by Carmen Bin Ladin published by warner books in New York, and its translation text entitled Kisah Hidupku di Arab Saudi by M. Yusdi, published by Pustaka Alvabet in Jakarta. The data are all the sentences which contained the adjective phrases. The technique of data collecting is a content analysis, i.e., the researcher read the texts (original and target) and write all the sentences that contained the adjective phrases. In a validity data, the research uses a data triangulation. Then, the data are analyzed with an interactive model, including data reduction, data display, and conclusion or verification. The findings of the research show that from the total 86 data, first, there are 65 data or 75, 58% which belong to accurate and there 21 data or 24,42% which belong to inaccurate. Second, there are 71 data or 82, 56% which belong to clear and 15 data or 17, 44% belong to unclear. And third, there are 79 data or 91, 86% which belong to natural and 7 data or 8, 14% belong to unnatural.